High-Performance All-Solid-State Lithium–Sulfur Batteries Enabled by Slurry-Coated Li6PS5Cl/S/C Composite Electrodes - Zheng, Chao; Wang, Kai; Li, Lujie; Huang, Hui; Liang, Chu; Gan, Yongping; He, Xinping; Zhang, Wenkui; Zhang, Jun (Frontiers in Energy Research, 2021)
Among many lithium secondary batteries, lithium–sulfur batteries stand out by high theoretical specific energy, low cost, non-toxic and no environmental pollution. However, due to poor electronic and ionic conductivity, shuttle effect, lithium dendrites and other defects, it remains a big challenge to achieve large-scale application of lithium-sulfur batteries. Here we report an all-solid-state lithium–sulfur battery based on Li-argyrodite Li6PS5Cl solid-state electrolytes through a slurry-coating method. Li6PS5Cl with a high ionic conductivity of 1.3 × 10−3 S cm−1 at room temperature is used as the solid electrolyte and the ion conductive additive in the electrode. The sulfur-based composite cathode is fabricated through a slurry-coating process by dispersing sulfur, Li6PS5Cl, ethyl cellulose and carbon black in 1,3-dioxolane (DOL). This method can disperse well the Li6PS5Cl around sulfur particles, and the solvent does not react with any component of composite cathodes during preparation. The battery delivered a high discharge capacity of 962 mA h g−1 at RT for the first cycle at 80 mA g−1. And the Coulombic eﬃciency is approximately 99.5% during 100 cycles. This work provides a new insight into the combination method between the sulfide-type SSEs and sulfur cathodes, which is critical to the electrochemical performance of all-solid-state lithium-sulfur batteries.